2007
DOI: 10.1210/me.2006-0069
|View full text |Cite
|
Sign up to set email alerts
|

Hypermetabolism of Fat in V1a Vasopressin Receptor Knockout Mice

Abstract: [Arg8]Vasopressin (AVP) has an antilipolytic action on adipocytes, but little is known about the mechanisms involved. Here, we examined the involvement of the V1a receptor in the antilipolytic effect of AVP using V1a receptor-deficient (V1aR-/-) mice. The levels of blood glycerol were increased in V1aR-/- mice. The levels of ketone bodies, such as acetoacetic acid and 3-hydroxybutyric acid, the products of the lipid metabolism, were increased in V1aR-/- mice under a fasting condition. Triacylglyceride and free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 39 publications
1
77
0
Order By: Relevance
“…A different KO line of the Avpr1a demonstrates a lower basal blood pressure (Egashira et al, 2004;Koshimizu et al, 2006) and impaired lipid metabolism and glucose homeostasis Hiroyama et al, 2007). Both lines have changes in behavior as discussed below.…”
Section: Gene Inactivation In Micementioning
confidence: 99%
“…A different KO line of the Avpr1a demonstrates a lower basal blood pressure (Egashira et al, 2004;Koshimizu et al, 2006) and impaired lipid metabolism and glucose homeostasis Hiroyama et al, 2007). Both lines have changes in behavior as discussed below.…”
Section: Gene Inactivation In Micementioning
confidence: 99%
“…Recent studies using knock-out mice have begun to reveal the physiological role of AVP and oxytocin in the CNS. V1a receptor knock-out (V1aR Ϫ/Ϫ ) mice showed abnormalities in spatial memory (Egashira et al, 2004), social interaction and anxiety (Bielsky et al, 2005;Egashira et al, 2007), and metabolism (Hiroyama et al, 2007). Oxytocin knock-out mice revealed that oxytocin plays an important role in social cognition and social, sexual, and maternal behavior (Winslow and Insel, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The V1a receptor (V1aR) is widely expressed, while the V1bR and V2R are predominantly expressed in the anterior pituitary gland and the kidney, respectively (7,13,17,20). V1aR mediates vascular contraction, cellular proliferation, platelet aggregation, glycogenolysis, lipid metabolism, and glucose tolerance (1,8,10). The V2R is expressed in the thick ascending limbs of Henle's loop (TAL) and the collecting ducts in the kidney (37).…”
mentioning
confidence: 99%